Micro-differences in local resource management: the case of honey in West Kalimantan, Indonesia - Jong, W. de (2000)
This paper discusses two cases of honey procurement in the province of West Kalimantan, Indonesia. Both involve the same resource, i.e. honey from Apis dorsata bees. However, in each case this resource is handled differently, showing that local resource management practices may be very site specific. Any local resource management practices involve local technological knowledge, but also social behavior, restrictions, and rules systems. The paper argues that such institutionalized resource management provides a sound basis for resource use that meets new challenges, such as achieving sustainable use or increasing monetary incomes. The possible practical implications depend on the particularities of each individual case. The first case this paper examines is honey tree management among the Maté-maté Dayak, who make up one of the Bidayuh language groups living in the district of Sanggau, Central West Kalimantan. These people can own single honey trees that are inhabited by bees; they protect the trees and encourage bees to nest in them. The second case involves honey procurements by Malay who live in the Danau Sentarum lake area, in the district of Kapuas Hulu, about 250 km east of the Maté-mate Dayak. Here, apiculturists assemble specially shaped boards that are popular nesting sites for A. dorsata bees. Once a swarm finds such a board, it continues to occupy the same board in successive years. Both Dayak and Malay beekeepers have an elaborate set of rules that regulate access to the trees and the nesting sites and impose fines for the breaking of such rules.